2009
DOI: 10.1080/07373930802566036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pretreatment and Drying on Composition and Bitterness of High-Dietary-Fiber Powder from Lime Residues

Abstract: Lime residues after juice extraction were used as a starting raw material to produce high-dietary-fiber powder. The effects of pretreatment-i.e., blanching and ethanol soaking (55-95% v/v)-and hot air drying at 60-100 C on the proximate composition and limonin, a substance responsible for bitterness in citrus fruits, were evaluated. Hydration properties-i.e., water retention capacity and swelling capacity-and visual color were also determined. It was found that using selected pretreatments in combination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 42 publications
(51 reference statements)
4
33
0
1
Order By: Relevance
“…Previous reports revealed that WSC of DFs from bamboo shoots were higher than that of deoiled cumin (7.98 mL/g) (Ma and Mu, 2016) and defatted rice bran (6.08 mL/g) (Hu et al, 2009), but similar to that of Zizyphus mauritiana fruits (19.34 mL/g) (Sangeethapriya and Siddhuraju, 2014). Several Studies also suggested that smaller particle size, larger surface area, the content of SDF and IDF and lower bulk density might have contributed to higher WSC (Lan et al, 2012;Wuttipalakorn et al, 2009). Our results indicated that extraction methods also affect the value of WSC.…”
Section: Water Swelling Capacitymentioning
confidence: 98%
See 1 more Smart Citation
“…Previous reports revealed that WSC of DFs from bamboo shoots were higher than that of deoiled cumin (7.98 mL/g) (Ma and Mu, 2016) and defatted rice bran (6.08 mL/g) (Hu et al, 2009), but similar to that of Zizyphus mauritiana fruits (19.34 mL/g) (Sangeethapriya and Siddhuraju, 2014). Several Studies also suggested that smaller particle size, larger surface area, the content of SDF and IDF and lower bulk density might have contributed to higher WSC (Lan et al, 2012;Wuttipalakorn et al, 2009). Our results indicated that extraction methods also affect the value of WSC.…”
Section: Water Swelling Capacitymentioning
confidence: 98%
“…DFs form food components (cellulose, hemicelluloses and lignin), non-digestible constituents in the cell walls of plants, fractions of food (polysaccharides and lignin) as well as non-digestible oligosaccharides (Mccleary et al, 2010). Epidemiological studies suggested that DFs consumption can help in maintaining the functional integrity of the gastrointestinal system, and reducing colon cancer and heart disease (Davidson and Mcdonald, 1998) which are related to physicochemical and functional properties of DFs depending on the food sources, extraction methods, chemical composition, structure, and particle size of DFs (Peerajit et al, 2012;Wuttipalakorn et al, 2009). Therefore, it is recommendable to explore new sources of DFs.…”
Section: Introductionmentioning
confidence: 99%
“…SDF has physiological effects, e.g., enhances satiety, regulates and improves the intestinal microflora, reduces the re-absorption of bile acids and the intestinal absorption of carbohydrates, and prevents diabetes and other cardiovascular diseases (Galisteo et al, 2008). Recent studies have reported that the physicochemical and functional properties of DFs, which are mostly derived from cereals, vegetables, and fruits (Abdul-hamid & Luan, 2000;Chau, Wang, & Wen, 2007;Fernando, Maria, Ana-Maria, Chiffelle, & Asenjo, 2005), depend on the food sources, extraction methods, chemical composition, structure, and particle size of DF (Martínez et al, 2012;Peerajit et al, 2012;Wuttipalakorn, Srichumpuang, & Chiewchan, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…The drying time at 45 °C (the central point) was in the range of 20-25 h. García-Perez et al (2009) and Ortuño et al (2010) studied the influence of applied acoustic energy on the convective drying kinetics at 40 °C assisted by power ultrasound of lemon and orange peels and reported drying times between 3 and 7 h according to the applied acoustic power density. Wuttipalakorn et al (2009) showed drying times of lime peels undergoing hot air drying at 80 °C between 4 and 6 h, depending on the ethanol concentration of the pretreatment solution used to reduce the initial moisture content of the samples. Garau et al (2007) assessed the convective drying kinetics of dried orange peels between 30 and 90 °C and established drying times of 8.3 h at 30 °C and 2.5 h at 60 °C.…”
Section: Drying Curvesmentioning
confidence: 99%